Charging ahead: Prepaid metering, electricity use, and utility revenue - Jack, Kelsey and Smith, Grant (American Economic Journal: Applied Economics)
Monthly bills for services such as electricity often go unpaid in developing countries. Prepaid meters offer a potential technological solution. In Cape Town, South Africa, over 4,000 residential customers on monthly billing were switched to prepaid metering, with random variation in the timing of the switch. In response, electricity use falls by 14 percent, driven at least in part by an increase in marginal price sensitivity. The decrease in revenue to the municipal electric utility is more than offset by lower revenue recovery costs. Switching poorer and more in-debt customers generates the greatest net revenue gains to the utility. - Reproduced
Keywords: Developing countries, South Africa